If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12-(35-3x)=34
We move all terms to the left:
12-(35-3x)-(34)=0
We add all the numbers together, and all the variables
-(-3x+35)+12-34=0
We add all the numbers together, and all the variables
-(-3x+35)-22=0
We get rid of parentheses
3x-35-22=0
We add all the numbers together, and all the variables
3x-57=0
We move all terms containing x to the left, all other terms to the right
3x=57
x=57/3
x=19
| x3-16x=0 | | m=700/3000-625 | | -7r+8-r=-9r+10 | | x=1.025 | | -5y+7=4-7y | | 3x+4/2x=5 | | (x+4)/2=6 | | 2^2^2^2^2^2^2^2=x | | 4/x-1=-4 | | 3d=243 | | 8(v+9)+8=10v-4 | | 7x÷2x=5 | | -3x+45=105 | | 3(2x+3)/2=x | | 2.3=3.7-0.7x | | 7x/2x=5 | | 2s=128 | | 6(x-9)=3x-2 | | 5p+2=4p-1 | | 6(x-9)=3x=2 | | 3.7=4.9-0.2x | | 4(2x-1)=3x+6# | | -12=8a | | 6*4+5*x=35 | | 3+7x-15x=27 | | 2x-(+2.9)=x-35 | | .15x=200 | | x^2/3-7x=1 | | (x+1)(-5x-4)=-4 | | x-18-22=12 | | x-18-22=30 | | 1-3(n+5=-8 |